Endogenous Ca2+ release was involved in 50-Hz MF-induced proliferation via Akt-SK1 signal cascade in human amniotic epithelial cells. (3rd April 2022) - Ye, an-Fang; Liu, Xiao-Chen; Chen, Liang-Jing; Xia, Yong-Peng; Yang, Xiao-Bo; Sun, Wen-Jun
ABSTRACT: The mechanism underlying the biological effects caused by an extremely low-frequency electromagnetic field (ELF-EMF) is still unclear. Previously, we found that L-type calcium channel and sphingosine kinase 1 (SK1) were involved in 50-Hz MF exposure-induced cell proliferation. In the present study, the role of intracellular Ca 2+ and signal molecules related to SK1 in cell proliferation induced by 50-Hz MF was investigated in human amniotic epithelial (FL) cells. Results showed that the intracellular Ca 2+ chelator, BAPTA, could completely inhibit 50-Hz MF-induced cell proliferation, whereas NIF, the inhibitor of L-type calcium channel, only partly blocked it. When cells were cultured in calcium-free medium, MF exposure also increased intracellular Ca 2+, activated SK1 and promoted cell proliferation although all of those increasing levels were lower than those in complete medium. Moreover, MF-activated SK1 could be completely inhibited by BAPTA, and MF-induced cell proliferation was abolished by SKI II, the specific inhibitor of SK1. Additionally, a 50-Hz MF exposure did not affect the activation of ERK and PKCα under the condition of calcium-free medium, but activated the Akt, which could be precluded entirely by BAPTA, but not be inhibited by NIF. Treatment of FL cells with LY294002, the inhibitor of Akt, could delete the MF-induced SK1 activation under the condition of calcium-free medium. Based on the data from the present experiment, it is concluded that endogenous Ca 2+ release was involved in 50-Hz MF-induced cell proliferation via Akt-SK1 signal cascade.